A Phase II, Randomised, Double-Blind, Placebo-Controlled Study to Evaluate the Efficacy of HEX17, a Novel Broad-Spectrum Antiviral Drug, in a Controlled Human Infection Model of Influenza Challenge - Geoff Kitson; Marion Byford; Lindsey Cass; David Howat; Brigitte Köhn; Alessandra Bisquera; Andrew Catchpole; Nicolas Noulin; Douglas Thomson (Infectious Diseases and Therapy)
Abstract Introduction Viral respiratory tract infections are of global concern, with an unmet need for a broad-spectrum antiviral prophylactic. HEX17, a multivalent carbohydrate-binding module, binds to sialic acid, a cell surface glycan used by many viruses for host cell entry. HEX17 represents a potential broad-spectrum antiviral prophylactic therapy. Methods This phase II randomised double-blind, placebo-controlled study was conducted in a UK centre. Healthy adults (18–55 years) were randomised (3:3:4) to daily HEX17 for 3 days (2.8 mg HEX17 from day − 3 to − 1); single-dose HEX17 (2.8 mg HEX17 on day − 3; placebo on day − 2 and − 1); or daily placebo (day − 3 to − 1). Participants were challenged with influenza virus on day 0 and assessed from days 1 to 8. Primary outcomes were incidence and severity of symptomatic influenza in the pooled HEX17 arms versus placebo, in the per protocol population (PPP). Safety analysis included all participants receiving at least one dose of HEX17/placebo. Results Of 104 participants enrolled between August 2022 and March 2023, 99 were included in the PPP (single-dose HEX17, n = 29; daily HEX17, n = 30; placebo, n = 40). Symptomatic influenza occurred in 16/40 (40.0%) participants in the placebo arm versus 12/59 (20.3%) in the pooled HEX17 arms (− 19.7% decrease; 95% confidence interval [CI] − 38.0, − 1.3; p = 0.0331). The median peak total symptoms score was 3.00 in the placebo arm and 2.00 in the pooled HEX17 arms (versus placebo: 95% CI − 2.00, 0.00; p = 0.1427). Unsolicited adverse events (AEs) occurred in 17/41 (41.5%), 10/32 (31.3%), and 9/31 (29.0%) participants in placebo, daily HEX17, and single-dose HEX17 arms, respectively (safety population). No deaths or serious AEs occurred. Conclusion Prophylactic HEX17 reduced the incidence of symptomatic influenza infection and may protect at-risk patients against influenza infection. Trial Registrations EudraCT 2022-001853-22, Clinicaltrials.gov NCT05507567.